A comprehensive analysis of transient pressure and rate data from CO2 storage projects in a depleted pinnacle reef oil field complex, Michigan, USA. (May 2021) - Mishra, Srikanta; Kelley, Mark; Raziperchikolaee, Samin; Ganesh, Priya Ravi; Valluri, Manoj; Keister, Laura; Burchwell, Andrew; Mawalkar, Sanjay; Place, Matt; Gupta, Neeraj; Pardini, Rick
Highlights: Application of three approaches for analyzing transient pressure and rate data from CCUS projects in depleted reef reservoirs in Michigan, USA. Methods are: injection-falloff, injectivity/productivity index, and pressure pulse arrival time analysis. All three methods widely used in oil industry; but latter two hitherto not used for CCS projects. Theory behind each technique presented and its applicability demonstrated via illustrative examples from multiple wells in different reefs. Discussion of the relative merits of each interpretive technique, as well as recommendations that could be useful for other field projects. Abstract: Pressure and rate data are commonly recorded as part of a basic monitoring program in CCS projects. This paper discusses the application of multiple analytical techniques to interpret pressure and rate transient data from CO2 injection and storage operations. The techniques of interest, i.e., injection-falloff analysis, injectivity/productivity index analysis and pressure pulse arrival time analysis, are commonly used in the oil and gas industry to assess reservoir properties, but not well known in the CCS literature (especially the last two). Injection-falloff analysis involves log-log pressure derivative plotting for the falloff data and history-matching of the entire injection-falloff sequence to determine permeability. In the injectivity/productivity index analysis, rate-normalized pressure buildup is plotted against material balance time or ratio of cumulative injection to injection rate to determine the injectivity index (ratio of injection rate to stabilized pressure buildup) which can be related to the permeability-thickness product. The arrival time analysis identifies the arrival of a pressure disturbance (∼0.1 psi change from ambient) to determine the hydraulic diffusivity from which permeability can be estimated. The applicability of these techniques is demonstrated via illustrative examples from multiple wells in different pinnacle carbonate reefs undergoing CO2 -EOR in Northern Michigan. The paper ends with a discussion of the relative merits of each interpretive technique, as well as recommendations that could be useful for other field projects.